2008
DOI: 10.1002/pbc.21869
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chemotherapy on neurocognitive function in children with acute lymphoblastic leukemia: A critical review of the literature

Abstract: Chemotherapy-only treatment has increasingly become the standard of treatment for childhood acute lymphoblastic leukemia (ALL). The objective of this review is to assess the present state of knowledge of the neurocognitive effects of central nervous system (CNS)-directed chemotherapy in children with ALL, and to formulate directions for future research. We performed a review of studies published since 1997, that included an ALL group treated with chemotherapy only and a control group. Twenty-one studies met ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
143
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(160 citation statements)
references
References 81 publications
10
143
0
7
Order By: Relevance
“…11-14 Conclusions from systematic reviews have been mixed, [16][17][18] largely because of reliance on qualitative methods to assess outcomes 18 and inclusion of studies with patients who had very recently completed therapy or without a control population. [16][17][18] Because neurocognitive impairment takes time to develop and/or be detected, early assessments are likely not adequate.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…11-14 Conclusions from systematic reviews have been mixed, [16][17][18] largely because of reliance on qualitative methods to assess outcomes 18 and inclusion of studies with patients who had very recently completed therapy or without a control population. [16][17][18] Because neurocognitive impairment takes time to develop and/or be detected, early assessments are likely not adequate.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Because neurocognitive impairment takes time to develop and/or be detected, early assessments are likely not adequate. Furthermore, because many of these neurocognitive measures are correlated with demographic factors, such as socioeconomic status, comparison with an appropriate healthy control group is particularly important.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 Antimetabolites and anthracyclines have been implicated. Although the association has long been established in childhood cancers, 41 emerging evidence shows a similar effect in TYAs. A retrospective study of more than 2500 cancer patients aged 11-21 identified deficiencies in emotional regulation, memory and task efficiency.…”
Section: Neurocognitive Effectsmentioning
confidence: 95%
“…Methotrexate is known to interfere with folate metabolism resulting in demyelination and other toxic effects on CNS thereby leading to cognitive decline. (67) Problems that are reported with the use of chemotherapy in treatment of pediatric brain tumors are problems with sustained attention, which correlated with teacher reports of poorer academic performance, particularly in mathematics, increased internalizing behaviors on the Child Behavior Checklist, a parent report measure of social competence and behavior problems, visual processing, visual-motor functioning, attention and executive functioning, academic performance, verbal abilities, and memory with female gender and young age (particularly less than age 3 years) as risk factors. (68-70) Psychopharmacological and palliative care interventions for neurocognitive effects:…”
Section: Sources Of Neurocognitive Deficitsmentioning
confidence: 99%